Effect of fish scales on fabrication of polyester composite material reinforcements - Abed Balsam H. (De Gruyter, 2021)
Renewable resources are used to create useful, biologically sustainable materials. It has the potential to minimize waste while also challenging existing research and developments. Several researchers have concentrated their efforts on natural fiber composites. Natural fibers include plant, mineral, and animal fibers. In this project fish scales, a bio-waste, were used as a reinforcing agent in polyester/polystyrene for the fabrication of composite materials in the different weight fractions of 0, 6, 7, 9, and 11%, at a constant load of 1 N and temperature of 20 and 26°C. The hand layup technique was used to create the fabrication setup for composite materials. The creep behavior, modulus of elasticity, and stress were studied experimentally.